The Effectiveness of Support Group Therapy on Depression and Anxiety Levels Among the Elderly in The Halim Subdistrict of East Jakarta - Widiastuti, Sri Hunun; Astuti, Harwina Widya; Amri, Khaerul; Pangaribuan, Santa Maria; Meylawati, Luluk Eka; Pujiastuti, Nawang; Anggraeni, Fitri (Nursing Current: Jurnal Keperawatan, 2025)
Aging is often accompanied by physiological, psychological, and social changes that increase the risk of mental health problems, particularly depression and anxiety. Effective psychosocial interventions are needed to help older adults manage these challenges and improve their well-being. This study aimed to determine the effect of Support Group Therapy on reducing depression and anxiety levels among older adults in Halim Village, East Jakarta. This study employed a quantitative quasi-experimental design with a pre-test–post-test approach. The sample consisted of 34 older adults selected using purposive sampling based on predetermined inclusion criteria. The intervention was delivered through 10 structured sessions, each focusing on specific topics related to emotional well-being and peer support. Data normality was tested using the Kolmogorov–Smirnov test, while statistical analysis was conducted using paired t-tests and independent sample t-tests. The results showed a significant difference (p < 0.001) in depression and anxiety levels before and after the intervention, indicating that Support Group Therapy is effective in reducing depression and anxiety among the elderly. These findings contribute to nursing practice, particularly in mental health nursing, by supporting Support Group Therapy as an effective psychosocial intervention to improve the mental health of older adults. This intervention may be implemented sustainably in community settings and health care facilities that provide services for the elderly.